Buckling capacity curves for steel spherical shells loaded by the external pressure = Krzywe nośności wyboczeniowej stalowych powłok sferycznych obciążonych ciśnieniem zewnętrznym - Błażejewski, Paweł; Marcinowski, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Assessment of buckling resistance of pressurised spherical cap is not an easy task. There exist two different approaches which allow to achieve this goal. The first approach involves performing advanced numerical analyses in which material and geometrical nonlinearities would be taken into account as well as considering the worst imperfections of the defined amplitude. This kind of analysis is customarily called GMNIA and is carried out by means of the computer software based on FEM.
Keywords: stalowe powłoki sferyczne; nośność wyboczeniowa; krzywe nośności; model numeryczny; MES; steel spherical shells; buckling resistance; capacity curve; numerical approach; FEM